Pedagogia e música: contribuições de Freinet para uma educação integrada no contexto do primeiro ano do ensino fundamental - Lins, Tales José Lopes (Universidade Federal de São Carlos, 2021)
This study was based on the motivation to seek solutions for more active and respectful practices for school children. We consider the school reality that is still fixed in the transmission of knowledge to be problematic, in the rigid structuring of the routine that favors mental tasks to the detriment of the child's total engagement. Thus, we sought to know the contributions of Celèstin Freinet's pedagogy, especially with regard to the experiences that involve the body, spontaneity and expressiveness. The context of the first year of elementary school was delimited, given the importance of this specific moment in child development. Music was valued as an integrating element of the knowledge expected for this stage and for its potential to recruit cognitive, physical, emotional and social skills in individual and collective conditions. A perspective of collaborative work between pedagogue and music teacher is assumed in order to ensure more cohesive experiences. The challenges of this cooperation are described based on a specific framework that has been discussing the presence of Art in Pedagogy courses. The study is characterized as bibliographic and qualitative and aims to: analyze the extent to which Freinet's principles dialogue with the document Read and Write: planning guide and didactic guidelines / 1st year literacy teacher from the State Department of Education of São Paulo; make activity proposals that consider all the languages provided for in the aforementioned document using music as a fundamental part of the learning expectations required for children and; stimulate and strengthen the integrated and collaborative work between educators and music teachers to obtain answers to the current educational needs. In this perspective, four didactic proposals were elaborated considering the contents foreseen for this school stage. The results indicated that it is possible to carry out plans that take into account children's needs, the current limitations of teacher training, in line with the principles of autonomy, work and free expression valued by Freinet. We understand that future practical opportunities may bring us more clarity on these propositions. The theoretical investigations carried out reinforce the importance of rethinking the education of the pedagogue in relation to the Arts and active approaches to Education.
Pedagogy and music: Freinet's contributions to integrated education in the context of the first year of fundamental education
Keywords: Pedagogia; Música; Celèstin Freinet; Pedagogy; Music; Celèstin Freinet; CIENCIAS HUMANAS::EDUCACAO